Efficient sequence of therapy for advanced and metastatic endometrial cancer - A. A. Rumyantsev (ABV-press, 2022)
Historical standard of the first line endometrial cancer therapy was combination of paclitaxel and carboplatin. In more than a half of patients with advanced endometrial cancer receiving this combination, disease progression is observed after 2 years. Use of paclitaxel + carboplatin combination in adjuvant therapy requires search for effective regimens for progression after this systemic therapy. Chemotherapy effectiveness in progression after systemic therapy is low with a small exception: repeat administration of paclitaxel + carboplatin can be used after long platinum-free period. In a quarter of all patients with progression after systemic treatment, use of pembrolizumab monotherapy in case of microsatellite instability (or abnormalities in DNA reparation system) showed significant clinical benefit. Additionally, most tumors do not have abnormal DNA reparation system, and multitarget tyrosine kinase inhibitor and checkpoint inhibitor combination is considered pathogenetically justified. The first and only such regimen described in Russian clinical guidelines is lenvatinib and pembrolizumab combination which showed clinical benefit in the form of increased overall survival.